(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: PCNL serves as the standard treatment for large renal stones though it typically leads to considerable blood loss from the procedure. Patients treated with the antifibrinolytic medication tranexamic acid experience decreased bleeding during surgical procedures and after surgery because this drug blocks the fibrinolytic process. Additional research studies need to explore the value of TXA for PCNL because its therapeutic potential has proved effective in other surgical specialties. Objective: This study aims to determine how intravenous administration of tranexamic acid impacts surgical bleeding amounts and transfusion rates together with post-operative hospital length of stay for patients who undergo PCNL. Methods: The study was executed as a randomized controlled trial in the Department of Urology at Liaquat National Hospital, Karachi for six months. The research enrolled 118 patients who received PCNL and distributed them randomly between two separate groups. The participants in Group A received 1g of intravenous tranexamic acid through an intravenous route exactly twenty minutes before the procedure began while Group B members got normal saline as their placebo treatment. Both pre-operative and post-operative assessments measured patients’ hemoglobin and hematocrit levels while recording the need for transfusions and determining the period of hospital stay. SPSS v16 handled the data analysis while p≤0.05 indicated statistical significance. Results: The TXA-treated patients showed a minimal reduction of mean hemoglobin levels which amounted to 1.0 ± 0.4 g/dL while mean hemoglobin levels in the placebo group descended to 1.9 ± 0.6 g/dL (p<0.001). The patients in Group A experienced a lower mean hematocrit loss percentage (2.8 ± 1.1%) than those in Group B (4.9 ± 1.4%) and this difference reached statistical significance (p<0.001). A total of 10.2% of patients receiving TXA needed transfusion therapy whereas 28.8% of placebo group patients needed transfusion therapy (p=0.01). Patients who received TXA spent 2.7 ± 0.8 days in the hospital while patients who received placebo required 3.4 ± 1.0 days (p=0.002). Patients experienced no negative side effects or signs of thromboembolic complications during the study period. Conclusion: Clinical administration of IV tranexamic acid reduces perioperative bleeding transfusion rates and hospitalization duration in patients undergoing arbuscular nephrolithotomy procedures while maintaining good safety outcomes. The use of intravenous tranexamic acid serves as a successful surgical tool that helps improve urological medical results.